Overview of Return Times for Inpatient Medical Records at Andalas University Hospital - Rahmadhani; Oktamianiza; Ade Puspitasari (CV. Get Press Indonesia, 2024)
One supporting element for medical record processing is the prompt return of files belonging to patients who have concluded their inpatient healthcare services. The established standard for the return of these medical records is within a maximum of 48 hours. This research aims to ascertain the timeframe the return of hospitalized patient records at Andalas University Hospital in Padang. The investigation employed a quantitative approach utilizing descriptive methods. The research took place in the storage room at Andalas University Hospital, Padang. The investigation took place starting from May to September 2023. The population of this study was 302 files with a sample of 75 medical record files with data collection time from 20 to 25 September 2023. The research applied the Simple Random Sampling technique. Data gathering involved observation and data processing techniques including editing, coding, processing, and cleaning. The analysis focused on univariate analysis. Results from Andalas University Hospital revealed that 31 files (41.3%) returned accurate medical records, while 44 files (58.7%) were found to have incorrect medical records returned. This indicates that many medical record files were returned after the stipulated timeframe of >48 hours. As a conclusion from the study, it's imperative for the head of the medical records room to assess and supervise the return process of inpatient medical record files. By doing so, this issue can be mitigated and delays in Submitting the medical records of a hospitalized patient anew files can be minimized.